2016
DOI: 10.3382/ps/pev353
|View full text |Cite
|
Sign up to set email alerts
|

Histology, composition, and quality traits of chicken Pectoralis major muscle affected by wooden breast abnormality

Abstract: Only a few years ago, the poultry industry began to face a recent abnormality in breast meat, known as wooden breast, which frequently overlaps with white striping. This study aimed to assess the impact of wooden breast abnormality on quality traits of meat. For this purpose, 32 normal (NRM), 32 wooden (WB), and 32 wooden and white-striped (WB/WS) Pectoralis major muscles were selected from the same flock of heavy broilers (males, Ross 708, weighing around 3.7 kg) in the deboning area of a commercial processin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

37
242
3
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 234 publications
(315 citation statements)
references
References 43 publications
37
242
3
5
Order By: Relevance
“…It is likely that, as previously observed in WS condition (Petracci et al 2014), the functional proteins content, responsible for meat WHC is lowered in favour of collagen (Dalle Zotte et al 2014;Petracci et al 2015). This hypothesis found confirmation in the work by Soglia et al (2016a), which showed a higher collagen and lower protein contents in chicken breast muscles affected by WB abnormality compared to normal ones. This replacement results in a significant impairment of protein functionality and water retention of cooked meat, despite collagen proteins shorten, swell, solubilize during the cooking process and gelatinize when cooled (Palka 1999;Tornberg 2005), thus keeping an amount of water.…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…It is likely that, as previously observed in WS condition (Petracci et al 2014), the functional proteins content, responsible for meat WHC is lowered in favour of collagen (Dalle Zotte et al 2014;Petracci et al 2015). This hypothesis found confirmation in the work by Soglia et al (2016a), which showed a higher collagen and lower protein contents in chicken breast muscles affected by WB abnormality compared to normal ones. This replacement results in a significant impairment of protein functionality and water retention of cooked meat, despite collagen proteins shorten, swell, solubilize during the cooking process and gelatinize when cooled (Palka 1999;Tornberg 2005), thus keeping an amount of water.…”
Section: Resultssupporting
confidence: 62%
“…Despite the results of a recent work by Soglia et al (2016a) showed that WB chicken breasts exhibited higher hardness, gumminess, and chewiness than normal ones, shear force values of the affected cooked breasts of the present experiment did not correspond to the palpatory hardness perceived at the fresh and thawed state; these results are in accordance with those of Mudalal et al (2015). The extensive poor cohesion and the tendency of the fibre bundles to separate, mainly at the cranial level, could have mitigated the expected hardness (Petracci and Cavani 2012;Petracci et al 2013).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Salt may contribute to the solubilisation of myofibrillar proteins (MPs), depolymerisation of myofilaments and dissociation of the actomyosin complex (Lo Nostro & Ninham, ). WB impairs the muscle structure and causes different MP patterns (Soglia et al ., ). Thus, determining the functional and technological properties of meat using various salt additions for the manufacture of comminuted products is significant.…”
Section: Introductionmentioning
confidence: 97%
“…Recent studies indicated that WB abnormality affects the quality and functional properties of meat considerably. For example, compared with raw normal fillets, raw WB fillets exhibit lower water holding capacity (WHC) and different chemical composition and protein functionalities (Soglia et al ., , ). Meanwhile, the use of WB in manufacturing finely comminuted products remains uncertain.…”
Section: Introductionmentioning
confidence: 99%